2007
DOI: 10.1073/pnas.0705270104
|View full text |Cite
|
Sign up to set email alerts
|

Native language governs interpretation of salient speech sound differences at 18 months

Abstract: One of the first steps infants take in learning their native language is to discover its set of speech-sound categories. This early development is shown when infants begin to lose the ability to differentiate some of the speech sounds their language does not use, while retaining or improving discrimination of language-relevant sounds. However, this aspect of early phonological tuning is not sufficient for language learning. Children must also discover which of the phonetic cues that are used in their language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
110
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(125 citation statements)
references
References 39 publications
13
110
1
Order By: Relevance
“…It is also consistent with the recent finding that language-specific phonology influences the development of infants' speech perception (Mugitani et al, 2009). At first blush, our findings appear to contradict Dietrich et al (2007), in which English-learning 18-month-olds failed to link two novel objects with the two stimuli differing only in vowel duration. However, there is good reason to suspect that older infants are less likely to discriminate auditory patterns in a word-learning context than in a pure preference or discrimination task (Stager and Werker, 1997).…”
Section: Discussionsupporting
confidence: 35%
See 1 more Smart Citation
“…It is also consistent with the recent finding that language-specific phonology influences the development of infants' speech perception (Mugitani et al, 2009). At first blush, our findings appear to contradict Dietrich et al (2007), in which English-learning 18-month-olds failed to link two novel objects with the two stimuli differing only in vowel duration. However, there is good reason to suspect that older infants are less likely to discriminate auditory patterns in a word-learning context than in a pure preference or discrimination task (Stager and Werker, 1997).…”
Section: Discussionsupporting
confidence: 35%
“…Recently, Dietrich et al (2007) found that Dutch and English learning 18-month-olds treat vowel duration differently in a word learning task. In Dutch, vowel duration is an important cue for differentiating the low vowels [Ä] and [ab], whereas in English, it is only a secondary cue to distinguish a tense from a lax vowel.…”
Section: Introductionmentioning
confidence: 99%
“…Although it was initially hypothesized that infants learn sounds from contrastive meanings, i.e., minimal pairs (Werker & Tees, 1984), this idea was challenged by the finding that infants are sensitive to language-specific phonetic detail at an age at which they hardly know any words, let alone enough minimal pairs to allow for all contrasts (e.g., Caselli et al, 1995;Dietrich, Swingley, & Werker, 2007). Instead, current theories of first language acquisition argue that perceptual reorganization occurs mainly through bottom-up learning from speech input (e.g., Kuhl et al, 2008;Pierrehumbert, 2003;Werker & Curtin, 2005).…”
Section: Distribution-driven Learning Of Perceptionmentioning
confidence: 99%
“…Also, Dutch orthography, in contrast to English, clearly marks durational oppositions, as in maan ("moon") and man ("man"), rules that are very familiar to literate Dutch adults. Finally, Dutch unlike English speakers have been reported to be reluctant to exaggerate the duration of short vowels to convey emphasis in child-directed speech (Dietrich et al, 2007). In most dialects of English vowel duration is not considered contrastive, though vowels vary in their "intrinsic" durations (House, 1961;Chomsky and Halle, 1968;Hillenbrand et al, 2000) and duration varies depending on context, as will be discussed in more detail below.…”
mentioning
confidence: 99%